(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
The study assessed the awareness of female traders at a lorry station in Kumasi, Ghana about the adverse effects of automobile emissions on their health. A cross-sectional survey design with a semi-structured interview was used to collect data from all 48 traders who sell at the station. The results indicated that the traders believed all automobile emissions have a smell, are visible and blue in colour. The findings also showed that 47.9% of the traders knew automobile emissions cause irritation of the eyes, 43.7% felt the emissions cause coughing and 31.3% attributed nausea and vomiting to the inhalation of the emissions. It was concluded that the traders were aware of some of the adverse effects of automobile emissions. They were, however, not aware that the inhalation of the emissions could result in death. The study recommended that the local authority (Kumasi Metropolitan Assembly) should relocate either the lorry station or the female traders to save the latter from inhaling dangerous emissions. The Environmental Protection Agency should also embark on vigorous education of the general public on the adverse effects of automobile emissions